Wound Healing Activity of a New Formulation from Platelet Lysate - Akram Jamshidzadeh; Omid Koohi Hosseinabadi; Reza Heidari; Soliman Mohammadi Samani; Sara Rajabzadeh; Seyed Mojtaba Seyed Raoufi; Alireza Ahmadi Vadeghani (Shiraz University of Medical Sciences, 2016)
Platelet-rich plasma (PRP) is an attractive preparation in regenerative medicine due to its potential role on the healing process in different experimental models. This study was designed to investigate the wound healing activity of a new formulation of PRP. Different gel-based formulations of PRP were prepared. Open excision wounds were made on the back of male Sprague-Dawley rats, and PRP gel was administered topically once daily until the wounds healed completely (12 days). The results revealed that the tested PRP formulation significantly accelerated the wound healing process by increasing the wound contracting, tissue granulization, vascularization, and collagen regeneration. Interestingly, we found that there were no significant differences between PRP formulation and its gel base in all above mentioned parameters. Although this investigation showed that PRP formulation had significant wound healing effects, but the PRP gel base also had significant wound healing properties. This might indicate the wound healing properties of the PRP gel ingredients in the current investigation.